Study of the thermodynamic characteristics of gold nanoparticles in the processes of melting and crystallization by the molecular dynamics method - Tsydypov, D. G.; Nomoev, A. V.; Garmaev, B. Z. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2025)
The article presents the results of computer modeling of melting and crystallization processes of spherical gold nanoparticles. The molecular dynamics method was used to analyze the thermodynamic characteristics (temperature, heat, entropy of melting, and crystallization) of nanoparticles for different heating and cooling rates. Such studies allow choosing the most suitable temperature ranges for the formation of nanocrystalline structures and predicting their sizes. Reducing the size of gold nanoparticles (less than 100 nm) leads to a significant increase in the ratio of the surface area to the volume of particles, as a result of which the physical and chemical characteristics of the material change significantly compared to materials of the same material in bulk form. Interest in gold nanoparticles is due to enhanced photoemission, high electrical and thermal conductivity, and increased catalytic activity of the surface. Gold nanoparticles have strong optical absorption and scattering properties in the visible region of the spectrum due to surface plasmon oscillations of free electrons. In the known studies from the literature, it was found that with an increase in the size of nanoparticles, the hysteresis between the melting and crystallization temperatures increases, while in theory the macroscopic melting and crystallization temperatures should be the same. The novelty of the study presented in this paper is to reveal a previously unobserved tendency for macroscopic temperatures, heat and entropy of melting and crystallization to converge with a decrease in the heating and cooling rates. The classical molecular dynamics method was used to study the thermodynamic properties of gold nanoparticles. The subject of modeling was gold nanoparticles of various sizes, spherical in shape with a face-centered cubic lattice. In the modeling process, the interatomic potential was used corresponding to the embedded atom method which was developed for gold, using an improved force matching methodology. Heating and cooling of nanoparticles were modeled at temperature change rates of 0.1 TK/s, 1 TK/s, 3 TK/s. By analyzing the relationship between the potential energy of gold nanoparticles and temperature, the dependences of the melting and crystallization temperatures of nanoparticles on their size were revealed. A relationship was established between the size of nanoparticles, heat, entropy of melting and crystallization at different heating and cooling rates. It was shown that with a decrease in the heating and cooling rates from 3 TK/s to 0.1 TK/s, there is a convergence of the macroscopic values of the melting and crystallization temperatures (a decrease in the difference from 467 K to 158 K), macroscopic values of the heat of melting and crystallization (from 4.24 kJ/mol to 0.67 kJ/mol), entropy of melting and crystallization (from 1.99 J/(mol·K) to 0.16 J/(mol·K)). It was assumed that this is due to a decrease in the proportion of the formed nanostructures other than face-centered cubic ones. Prediction of temperature regimes of melting and crystallization of gold nanoparticles allows controlling phase transitions in the production of nanocrystals with specified properties. This phenomenon can find application in microelectronics for the formation of thin films with a high degree of homogeneity and in catalysis for the formation of nanoparticles with the required structures and properties. The obtained data can be used to verify the results of real experiments on phase transitions and to adjust molecular dynamics models.